PROMOTING INCLUSIVE ENGLISH LANGUAGE LEARNING AT TAUFIQUL MUBAROK ORPHANAGE IN MUARA ANGKE, NORTH JAKARTA - Recard, Michael Recard; Cendana, Wiputra; Shoreamanis, Meicky; Sativa, Riza; Winardi, Yonathan; Agustin, Atalya (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
Taufiqul Mubarok, an orphanage in North Jakarta, is home to numerous orphans who attend school ranging from Kindergarten to Senior High School. These children, who are the primary residents of the orphanage, face significant educational challenges, particularly in English, due to limited access to quality education exacerbated by the high poverty levels in the area. In response, the Faculty of Education at Universitas Pelita Harapan (FIP UPH) and the Sunda Kelapa Sectoral Police (Polsek) initiated an English Learning Program to foster inclusive language education. The program aimed to provide these children with opportunities for educational advancement and, ultimately, a better quality of life than their parents. The English Learning Program, conducted from March to June 2024, adopted a holistic approach to support the comprehensive development of the orphanage residents. The program's methodology encompassed problem identification, preparation, implementation utilizing various teaching methods, appreciation, and evaluation. A competition was held at the program's conclusion to assess the participants' progress. The results demonstrated significant improvements in the children's English skills, highlighting the program's success.